Presence of MNPs in Water Environment-pathways of Degradation and Impact on Organisms - Zając, Marcin; Kotyńska, Joanna; Naumowicz, Monika (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In recent years, micro- and nanoplastics (MNPs) in the natural environment have become a severe issue. Therefore, it seems significant to be knowledgeable on the topic. The purpose of the literature review presented here is to describe the general characteristics of plastic particles, their main sources, degradation mechanisms, and the impact of plastic particles on individual systems of the human body.
Keywords: microplastics; nanoplastic; degradation; polymers; human health